Adsorption Study of Nitrate Anions by Different Materials Using Fixed Bed Column - Anaam Sabri; Noor Abbood (Engineering and Technology Journal, 2019)
MCM-41is, a mesoporous material with a hexagonal structure, has a high surface area, high pore vol., and low mass density. Continuous adsorption fixed bed of NH2-MCM-4I adsorbent was utilized for the removal of nitrate anions from aqueous solutions. The effect of adsorbent weight (0.5, 1, 2 gm), flow rate (0.5, 1.0, 1.5 ml/min) and initial NO3 - concentrations (50, 75, 100 mg/l) on breakthrough curves were studied. It was found that breakthrough time increases with increasing column bed height and decreases with increasing NO3 - inlet concentration and flow rate. The highest removal percentage (75.2%) achieved at inlet concentration of 100 mg/L of NO3 - anion, 1gm adsorbent weight and 1.5 mL/min flow rate. Thomas and Yan adsorption models showed a good fit to the experimental data. Removal of nitrate anion by traditional activated carbon was also investigated and the results were compared with the nitrate removal by NH2- MCM-41. It was concluded that NH2-MCM-41 is more efficient in nitrate removal than activated carbon and the maximum removal percentage of nitrate anions by traditional activated carbon was found to be 55.8%.